Room-temperature collagen mineralization material as well as preparation method and application thereof
By using fish bubbles as collagen material and simulating the process of collagen mineralization in bone tissue, mineralization and laminate forming of fish bubble materials are achieved at room temperature, which solves the problem of high cost of collagen materials and the inability to prepare bulk materials in the prior art, and realizes the preparation of high-performance and low-cost large-size bulk collagen mineralized materials.
Patent Information
- Application Number
- CN202411903877.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The collagen materials used for mineralization in the prior art are costly and cannot prepare bulk materials, which cannot meet the needs of industrial production.
Fish bubbles are used as collagen material, and the process of collagen mineralization in bone tissue is simulated, and the fish bubble materials are mineralized at room temperature, and stacked bonding and pressing are used to make block mineralized collagen materials.
It realizes the preparation of large-sized block collagen mineralized materials at room temperature, with excellent material performance and low cost, suitable for industrial mass production.
Smart Images

Figure CN119615609A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of bionic mineralized materials, and in particular to a room temperature collagen mineralized material and a preparation method and application thereof. Background Art
[0002] In the production process of building materials (ceramics, cement, etc.), a lot of energy is consumed, which will produce a lot of carbon emissions. A reliable direction to reduce carbon emissions in the preparation process is to learn from nature. After tens of thousands of years of evolution, many organisms have formed various structures with special functions. In addition, organisms often carry out a series of biochemical reactions at room temperature or even lower temperatures to form multi-level hard materials from micro to macro. This low-cost and efficient biological structure synthesis process provides people with new ideas for optimizing the current high-carbon emission synthesis technology. In recent years, Academician Fu Zhengyi of Wuhan University of Technology has proposed for the first time in the world to learn from the process of organizational structure formation in nature, so as to obtain inspiration to guide the synthesis of artificial materials, that is, "material preparation technology inspired by biological processes."
[0003] Biomineralization is the synthesis process of most minerals in organisms. Many hard materials with excellent performance, such as bones and tooth enamel, are formed through biomineralization. Take lightweight and high-strength bones as an example. In bones, mineralized collagen fibers are their basic building blocks. Nanohydroxyapatite grows in the confined space inside the collagen fibers and grows along the long axis of the fibers. The assembly of inorganic / organic two-phase substances in bones from the molecular scale to the macroscopic scale gives them excellent mechanical properties. In addition, researcher Ping Hang confirmed that prestress at the megapascal level is generated during the mineralization of collagen fibers. On the one hand, these mineralized fibers provide mineral content for the bones. On the other hand, they are like "prestressed steel bars", which prestress the entire bone and greatly improve its toughness.
[0004] By simulating the bone biomineralization process and preparing a suitable mineralization solution, the in vitro mineralization of collagen materials can be achieved. However, at present, the collagen materials used for mineralization are mostly one-dimensional collagen fibers and two-dimensional collagen films. The collagen concentration in these materials is low, and it is impossible to prepare bulk (three-dimensional) materials. The thickness of the collagen film is often only a few hundred nanometers, which is not easy to test mechanical properties, such as common tensile and other mechanical tests. In addition, the arrangement of collagen fibers in these materials is relatively disordered, which cannot be compared with the fineness of the arrangement of collagen fibers in bones. In addition, these collagen materials are difficult to obtain and expensive, which does not meet the requirements of actual industrial production.
[0005] Therefore, there is currently no method for preparing bulk materials at room temperature using low-cost, finely structured collagen materials for mineralization, and no basic process flow and process parameters have been found. Summary of the invention
[0006] The purpose of the present invention is to overcome the above technical deficiencies, provide a room temperature collagen mineralization material and a preparation method and application thereof, and solve the technical problems in the prior art that the collagen materials used for mineralization are high in cost and cannot be prepared in bulk form.
[0007] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a method for preparing a room-temperature collagen mineralized material, comprising the following steps: S1, pre-treating a fish vesicle material to obtain treated fish vesicles; S2, immersing the treated fish vesicles in a mineralizing solution for mineralization treatment, and drying to obtain a room-temperature collagen mineralized material.
[0008] In a second aspect, the present invention provides a room temperature collagen mineralization material obtained by the above preparation method.
[0009] In a third aspect, the present invention provides a block-shaped mineralized collagen material, comprising the above-mentioned room-temperature collagen mineralized material arranged in layers, and adhesive layers are arranged between the layers of the room-temperature collagen mineralized material.
[0010] In a fourth aspect, the present invention provides a method for preparing a block-shaped mineralized collagen material, comprising the following steps: using biological glue as a binder, laminating and pressing room temperature collagen mineralized materials to obtain a block-shaped mineralized collagen material.
[0011] Compared with the prior art, the beneficial effects of the present invention include: 1. The present invention uses fish vesicles as the collagen material for mineralization, which is not only easy to obtain and inexpensive, but also has a large material size that is conducive to processing; in addition, the collagen fibers in the fish vesicle material are arranged with high precision, comparable to bone tissue, and the material has good performance after mineralization; 2. The present invention simulates the process of collagen mineralization in bone tissue, prepares a mineralization solution in vitro, realizes the directional mineralization growth of nano-scale minerals in fish vesicle collagen fibers along the long axis of the fibers, makes full use of the interaction between organic / inorganic materials, further improves the mineral content and mechanical properties of the composite material, and the obtained mineralized fish vesicle material has good mechanical properties; 3. The present invention uses biological glue to bond multiple sheets of room temperature collagen mineralized materials together, thereby increasing the size of the material; and uses compression molding to increase the bonding strength between layers. Using a quick two-step process, the size of the material and the interface bonding effect are increased at room temperature, and a block-shaped mineralized collagen material with good mechanical properties is prepared; Therefore, the present invention can prepare large-sized block-shaped collagen mineralized materials at room temperature and has excellent mechanical properties. The fish vesicles used in the present invention are cheap, easy to obtain, and can be recycled. The mineralization process can be carried out at room temperature and pressure, and has strong potential for industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 are morphological images of materials prepared in Example 1 and Comparative Example 1; wherein A is an optical image of the unmineralized fish vesicles prepared in Comparative Example 1, B is an optical image of the mineralized fish vesicles prepared in Example 1, C is a physical image of the mineralized fish vesicles prepared in Example 1, D is a cross-sectional scanning electron microscope image of the unmineralized fish vesicles obtained in Comparative Example 1, and E is a cross-sectional scanning electron microscope image of the mineralized fish vesicles in Example 1; Figure 2 The TEM images are slices of the mineralized fish vesicles of Example 1 and the unmineralized fish vesicles of Comparative Example 1; A is Comparative Example 1 (low magnification), B is Comparative Example 1 (high magnification); C is Example 1 (low magnification), and D is Example 1 (high magnification); Figure 3 It is a transmission electron microscope image of the mineralized fish vesicle section in Example 1; wherein A is the mineralized collagen fiber in the fish vesicle; B is a high-resolution image of the white rectangular portion of A, and the inset is an enlarged image of the dotted rectangular portion in B; C is a selected area electron diffraction image of the white rectangular portion of A; Figure 4 The tensile test of the mineralized fish vesicles in Example 1 and the unmineralized fish vesicles in Comparative Example 1; wherein A is a tensile test curve, B is a comparison diagram of elastic modulus, C is a comparison diagram of ultimate tensile strength, and D is a comparison diagram of elongation at break; Figure 5 This is a thermogravimetric test diagram of the mineralized fish vesicles in Example 1; Figure 6 This is a physical picture of the block-shaped mineralized collagen material prepared in Example 1; A is a flat angle, and B is a hand-held angle; Figure 7 is a three-point bending test curve of the block-shaped mineralized collagen material in Example 1; Figure 8 The unmineralized block material obtained in Comparative Example 2 after cutting; Fig. 9 This is the displacement-load curve of the three-point bending test of the unmineralized bulk material in Example 2. DETAILED DESCRIPTION
[0013] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0014] The purpose of the present invention is to provide a room temperature collagen mineralization material and a preparation method and application thereof, by selecting fish vesicles which are easily available and inexpensive as collagen materials, simulating the process of biomineralization, and realizing the mineralization of fish vesicle materials at room temperature. Chitosan biological glue is used to bond multiple pieces of mineralized fish vesicles to increase the overall size of the material, and cold isostatic pressing is used to improve the bonding effect between the sheets.
[0015] In a first aspect, the present invention provides a method for preparing a room temperature collagen mineralized material, comprising the following steps: S1, pre-treating the fish bubble material to obtain treated fish bubble; S2, soaking the treated fish vesicles in a mineralization solution for mineralization treatment, and drying to obtain room temperature collagen mineralized material.
[0016] Preferably, in step S1, the pretreatment includes delipidation, decalcification and deproteinization.
[0017] Further preferably, the conditions for degreasing include: soaking in a NaOH solution with a concentration of 0.1 to 1 mol / L for 12 h to 48 h; the conditions for decalcification include: soaking in a HCl solution with a concentration of 0.1 to 1 mol / L for 12 h to 48 h; the conditions for removing impurities and proteins include: ultrasonic cleaning in a NaCl solution with a concentration of 0.1 to 1 mol / L for 10 min to 240 min.
[0018] More preferably, the fish bubble material is washed with deionized water before and after degreasing and decalcifying.
[0019] It is understandable that the processed fish foam can be cut into shapes as needed, and the operations are all conventional processing and are not specifically limited here.
[0020] Preferably, in step S2, the treated fish bubble is fixed on a fixture (stretched flat), and then immersed in a mineralizing solution for mineralization treatment. The present invention fixes the fish bubble on a fixture to keep it flat and ensure that it is completely immersed in the mineralizing solution, which is conducive to better mineralization and avoids wrinkles and bends that affect subsequent lamination.
[0021] Further preferably, the material of the clamp includes polypropylene, polytetrafluoroethylene material, etc.; which does not react with the components in the mineralization solution.
[0022] Preferably, in step S2, the mineralization solution is a mixture of a calcium source, a phosphorus source, a buffer, sodium chloride, polyacrylic acid and a solvent in a mass ratio of 1:(1-3):(4-8):(20-24):(0.1-0.5):(2200-2500). The present invention uses a calcium source, a phosphorus source and the like as raw materials, and forms a hydroxyapatite mineralization solution under the action of a buffer, sodium chloride, polyacrylic acid and the like; the internal mineralization of fish vesicle collagen fibers is achieved through the hydroxyapatite mineralization solution.
[0023] Further preferably, the calcium source includes calcium chloride dihydrate; the phosphorus source includes dipotassium hydrogen phosphate trihydrate; the buffer includes hydroxyethylpiperazine ethanesulfonic acid; and the solvent is water.
[0024] Preferably, in step S2, the conditions of the mineralization treatment include: the mineralization temperature is 25 to 40 ° C, the mineralization solution is replaced every 12 to 48 hours, and the total mineralization time is 3 to 7 days. The present invention increases the mineral content in the fish bubble material by regularly replacing the mineralization solution and extending the time of the mineralization reaction. In addition, as the mineralization temperature increases, the speed of the mineralization reaction can be accelerated; the extension of the mineralization cycle can increase the mineral content in the fish bubble. The increase in the mineral content in the fish bubble can improve its mechanical properties.
[0025] But it is worth noting that the mineral content does not increase indefinitely. First, the collagen fibers in the fish vesicles are limited. When all the fibers that can be mineralized have completed mineralization, it is meaningless to extend the mineralization time or temperature. Secondly, the mineralization process is affected by the already formed minerals. The generated minerals will affect the diffusion of the amorphous precursor, resulting in a lower mineralization rate in the later stage, or even stop. Therefore, the mineralization of the fish vesicle material can only reach a relatively stable level, that is, the content of minerals in the fish vesicles will increase very slowly or even not increase after reaching a value, that is, relatively complete mineralization. The parameters that can achieve relatively complete mineralization of the fish vesicle material are relatively broad. The present invention can achieve the mineralization of the fish vesicle material within the above-mentioned parameter range by controlling the conditions of the mineralization treatment. For the fish vesicles that have achieved relatively complete mineralization, the performance difference is not great in theory.
[0026] Preferably, in step S2, the drying conditions include: a temperature of 25 to 40° C. and a drying time of 12 to 48 hours. The present invention naturally dries the mineralized fish vesicles for subsequent use.
[0027] In a second aspect, the present invention provides a room temperature collagen mineralization material obtained by the above preparation method.
[0028] In a third aspect, the present invention provides a block-shaped mineralized collagen material, comprising the above-mentioned room-temperature collagen mineralized material arranged in layers, and adhesive layers are arranged between the layers of the room-temperature collagen mineralized material.
[0029] Preferably, the number of layers of the room temperature collagen mineralized material is 2 to 10. The number of bonding layers affects the size and some mechanical properties of the final block and can be selected according to actual application conditions.
[0030] In a fourth aspect, the present invention provides a method for preparing a block-shaped mineralized collagen material, comprising the following steps: The room temperature collagen mineralized material is laminated, bonded and pressed using biological glue as a binder to obtain a block-shaped mineralized collagen material.
[0031] Preferably, the bio-glue is prepared by mixing chitosan, acetic acid and solvent in a mass ratio of 1 g: (5-10) mL: (30-50) mL; the amount of bio-glue used is 0.03-1.3 mL / cm 2 The present invention can spin-coat a chitosan solution to laminate and bond multiple sheets of room temperature collagen mineralized materials together.
[0032] More preferably, the solvent is water.
[0033] Preferably, the compression molding is to put the laminated and bonded materials into a vacuum bag and evacuate the bag, and use a cold isostatic press (LDJ320 / 700-400, Sichuan Aviation Industry Chuanxi Machinery Factory) to increase the bonding strength between the sheets and enhance the interface bonding effect. The working pressure of the cold isostatic press is 100 MPa to 400 MPa, and the holding time is 5 to 30 min.
[0034] The invention opens up a new application of collagen waste. The biomineralization method can realize the preparation of large-sized materials at room temperature, waste utilization, and composite green production. In addition, the invented large-sized block-shaped collagen material has good mechanical properties and has a high application prospect in the future.
[0035] The present invention is further described in detail by specific embodiments. The fish bladder should be fresh and free from obvious discoloration and peculiar smell.
[0036] Example 1 A method for preparing a block-shaped mineralized collagen material comprises the following steps: S1, pretreatment and shape cutting of fish bubble material: wash the fresh fish bubble to remove blood, then soak it in 0.1 M NaOH solution for 24 h to remove fat; then wash the fish bubble with deionized water. Then soak the fish bubble in 0.1 M HCl solution for 24 h to remove possible calcium; then wash the fish bubble again with deionized water. Finally, soak the fish bubble in 0.1 M NaCl solution for ultrasonic cleaning for 10 min to remove impurities. The treated fish bubble material is cut into a circle with a diameter of 2 cm along the circular mold.
[0037] S2, mineralization of collagen fibers in fish vesicle materials: prepare hydroxyapatite mineralization solution, the mass of calcium chloride dihydrate, potassium dihydrogen phosphate trihydrate, hydroxyethylpiperazine ethanesulfonic acid, sodium chloride, polyacrylic acid and water in the mineralization solution are 0.04 g, 0.062 g, 0.238 g, 0.876 g, 0.01 g and 100 g, respectively. Fix the treated fish vesicle material on a polypropylene fixture and immerse it in the mineralization solution. The mineralization solution is replaced every 12 h, and the total mineralization reaction time is 7 days. Remove the mineralized fish vesicle from the fixture, rinse with deionized water, and then dry at 37 °C for 24 h to obtain room temperature collagen mineralized material (mineralized fish vesicle).
[0038] S3, using layer-by-layer stacking technology combined with cold isostatic pressing to prepare a block-shaped mineralized collagen material: add 1 mL of chitosan bio-glue to each piece of the room temperature collagen mineralized material (mineralized fish bubble disc, 2 cm in diameter) obtained in step S2, wherein the chitosan bio-glue is a mixture of 0.6 g chitosan, 5 mL glacial acetic acid, and 24.4 mL of water. After bonding 8 pieces of mineralized fish bubble discs into a whole, put them into a vacuum bag and evacuate them, and use a cold isostatic press to enhance the bonding between the layers. The working pressure of the cold isostatic press is 200 MPa, and the pressure holding time is 5 min.
[0039] Comparative Example 1 In order to study the morphology, structure and properties of fish vesicles before hydroxyapatite mineralization, and to prove that the mineralization solution can achieve the mineralization of fish vesicle materials, fresh fish vesicles were pre-treated and then dried directly without mineralization to obtain single unmineralized fish vesicles.
[0040] That is, the difference between Comparative Example 1 and Example 1 is that the mineralization treatment in step S2 and the multi-layer stacking treatment in step S3 are not performed, and the treated fish bubble material obtained in step S1 of Example 1 is directly used.
[0041] Comparative Example 2 In order to study the effect of mineralization on the properties of bulk materials, fresh fish vesicles were pre-treated and then dried directly without mineralization to obtain unmineralized fish vesicles, which were then stacked to prepare bulk materials.
[0042] That is, the difference between Comparative Example 2 and Example 1 is that the mineralization treatment of step S2 is not performed, and the fish bubble material obtained in step S1 is directly subjected to the multi-layer stacking treatment of step S3 to prepare a block material.
[0043] Performance Testing 1. The mineralized fish vesicles obtained in step S2 of Example 1 and the unmineralized fish vesicles obtained in Comparative Example 1 were characterized by optical microscopy. Figure 1 shown.
[0044] Depend on Figure 1 It can be seen that the surface of the fish bubble after mineralization in Example 1 is flat, and due to the growth of hydroxyapatite inside the fish bubble, the fish bubble becomes opaque ( Figure 1 B). The unmineralized fish vesicles obtained in Comparative Example 1 were transparent after drying ( Figure 1 A).
[0045] In Example 1, by cutting the fish vesicles into suitable shapes, the preparation of disc-shaped mineralized fish vesicle materials can be achieved, which can be used in subsequent processes ( Figure 1 C). The single mineralized fish vesicle prepared in Example 1 and the unmineralized fish vesicle obtained in Comparative Example 1 were characterized by scanning electron microscopy. The results are as follows: Figure 1 D and Figure 1 E. It can be found that Figure 1 In D, there are many adjacent collagen lamellae in the unmineralized fish lamellae obtained in Comparative Example 1, so it can be judged that the fish lamellae material is formed by the continuous stacking of many collagen lamellae. Figure 1 In E, in the scan image of the mineralized fish vesicle prepared in Example 1, adjacent collagen lamellae can still be seen, but a lot of hydroxyapatite can be seen growing inside, indicating that the fish vesicle material has been mineralized from the inside to the outside, but the basic structure has not changed.
[0046] 2. The single mineralized fish vesicle prepared in Example 1 and the unmineralized fish vesicle in Comparative Example 1 were subjected to the steps of tissue fixation, tissue dehydration, infiltration, embedding and polymerization, slicing and staining to prepare ultra-thin slices, so that electrons can penetrate the samples for observation under a transmission electron microscope (Talos F200S). The results are shown in FIG. Figure 2 shown.
[0047] It can be seen that in Figure 2 A and Figure 2 B shows that there are and scanning images in the unmineralized fish bubble structure in Comparative Example 1 ( Figure 1 D) The corresponding collagen microfibril layers, these layers are in close contact with each other. In the same layer of collagen layer, the arrangement direction of collagen microfibrils is the same, there are differences in the angles of the collagen microfibrils between adjacent layers, and the size of the collagen microfibrils is about 50 nm. Figure 2 C shows that the fibers inside the mineralized fish vesicle fibers become darker in color due to the filling of hydroxyapatite. Figure 2 D It can be seen that the mineralized hydroxyapatite exists in the form of needles inside the collagen fibers, and there is no hydroxyapatite mineral between the fibers, which indicates that the present invention achieves the internal mineralization of fish vesicle collagen fibers.
[0048] 3. The single mineralized fish vesicle prepared in Example 1 was prepared into ultrathin sections, and the arrangement of hydroxyapatite inside was observed using a high-resolution transmission electron microscope. Figure 3 shown.
[0049] Figure 3 B is a resolution transmission electron micrograph of the mineralized fish vesicle collagen fibers. The measured interplanar spacing of 0.34 nm is exactly the interplanar spacing of the (002) crystal plane of the HAP crystal, and the lattice fringes are arranged neatly and arranged in the same direction. Figure 3 The collagen fibers in A are arranged along the long axis, indicating that hydroxyapatite grows along the axial direction of fish alveolar collagen fibers. Figure 3 C is the selected area electron diffraction analysis of the fish vesicle mineralized collagen fiber. After calculation, analysis and comparison of the single crystal selected area diffraction pattern, it was determined that the crystal composition was hydroxyapatite, and the symmetry direction of the arc-shaped diffraction crystal planes (002) and (004) was exactly the direction of the long axis of the collagen microfiber, indicating that the HAP crystals grew in an oriented manner inside the fiber, and the growth direction was along the long axis direction of the collagen microfiber (c axis). The above proves that Example 1 achieves the directional growth of hydroxyapatite in the fish vesicle collagen fiber.
[0050] 4. The single piece of mineralized fish vesicle prepared in Example 1 (denoted as Mineralized) and the unmineralized fish vesicle prepared in Comparative Example 1 (denoted as Original) were cut into strips and tested with a universal testing machine (Instron 5967) to compare the difference in mechanical properties. Figure 4 .
[0051] Figure 4 A is a tensile curve of the mineralized fish vesicles in Example 1 and the unmineralized fish vesicles in Comparative Example 1. It can be seen from the figure that the mineralized fish vesicles in Example 1 show the properties of a brittle material compared to the unmineralized fish vesicles in Comparative Example 1. Figure 4 B shows that the elastic modulus of the mineralized fish vesicles in Example 1 is 1213.4±140.1 MPa, and the elastic modulus of the unmineralized fish vesicles in Comparative Example 1 is 430.6±162.1 MPa. The elastic modulus of the mineralized fish vesicles in Example 1 is 2.8 times higher than that of the unmineralized fish vesicles in Comparative Example 1. Figure 4 C shows that the ultimate tensile strength of the mineralized fish vesicles in Example 1 is 27.4±3.7 MPa, and the ultimate tensile strength of the unmineralized fish vesicles in Comparative Example 1 is 21.2±2.2 MPa. The ultimate tensile strength of the mineralized fish vesicles in Example 1 is 1.29 times higher than that of the unmineralized fish vesicles in Comparative Example 1. Figure 4D It can be seen that the elongation at break of the mineralized fish vesicles in Example 1 is about 5%, and the elongation at break of the unmineralized fish vesicles in Comparative Example 1 is about 15%. The mineralized fish vesicles in Example 1 have a shorter elongation at break than the unmineralized fish vesicles in Comparative Example 1, showing the characteristics of a brittle material. In summary, the mechanical properties of the mineralized fish vesicles in Example 1 are greatly improved compared with the unmineralized fish vesicles in Comparative Example 1, and the elongation at break is shorter, showing the characteristics of a brittle material.
[0052] 5. The single piece of mineralized fish vesicle prepared in Example 1 was subjected to thermogravimetric analysis. The results are as follows: Figure 5 It can be seen that after seven days of mineralization, the hydroxyapatite mineral content in the fish vesicles is about 60%.
[0053] 6. The block-shaped mineralized collagen material obtained by lamination and cold isostatic pressing in Example 1 is as follows: Figure 6 shown.
[0054] It can be seen that the block-shaped mineralized collagen material prepared by the three steps of the present invention has a diameter of 20 mm and also has a certain thickness, indicating that the present invention can prepare a macroscopic large-sized material at room temperature. The block-shaped material appears white due to the growth of hydroxyapatite inside.
[0055] 7. The block-shaped mineralized collagen material prepared in Example 1 was cut into strips with a length of 20 mm and a width of 2 mm, and subjected to a three-point bending test using a universal testing machine. The results are as follows: Figure 7 As shown, the flexural strength and elastic modulus are a series of average values taken from three tests.
[0056] Depend on Figure 7 It can be calculated that the flexural strength of the block prepared by the present invention is 51.89 MPa±9.54 MPa, and the elastic modulus is 3.00 GPa±1.15 GPa.
[0057] 8. The unmineralized block material prepared in Comparative Example 2 is also cut into pieces, such as Figure 8 As shown; then a three-point bending test was performed, and the results were as follows Fig. 9 shown.
[0058] Depend on Figure 8 and Fig. 9 The results show that the unmineralized material is yellow and relatively transparent. During the sample test, the curve did not drop before reaching the maximum range of the instrument, and the bending resistance was very poor, indicating that the unmineralized sample showed the characteristics of typical organic materials. Although it has toughness, it does not have the characteristics of brittle materials. It can be bent with very small force, so its use scenarios are limited.
[0059] The present invention fills the gap in the preparation method of room temperature bulk collagen mineralized materials, and solves the problems of size, mechanical properties, and preparation economic benefits of collagen mineralized materials in the prior art. The present invention realizes the preparation of room temperature bulk collagen mineralized materials at room temperature, and uses fish vesicle materials, which are waste materials in industrial production, as a matrix, and simulates the bone mineralization process in vivo to realize the internal mineralization of fish vesicle materials, and then uses a lamination process to prepare large-sized materials. The preparation method of the present invention is convenient and simple, green and environmentally friendly, and has high economic benefits. It is suitable for mass production, and the produced materials have good mechanical properties and are expected to be used as biological scaffold materials, tissue regeneration materials, and tissue replacement materials. The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing room temperature collagen mineralized material, characterized in that: The following steps are involved: S1, pre-treating the fish bubble material to obtain treated fish bubble; S2, soaking the treated fish vesicles in a mineralization solution for mineralization treatment, and drying to obtain room temperature collagen mineralized material.
2. The method for preparing room temperature collagen mineralization material according to claim 1, characterized in that: In step S1, the pretreatment includes delipidation, decalcification and deproteinization; The degreasing conditions include: soaking in a NaOH solution with a concentration of 0.1 to 1 mol / L for 12 to 48 hours; The decalcification conditions include: soaking in a 0.1-1 mol / L HCl solution for 12 h to 48 h; The conditions for removing impurities and proteins include: ultrasonic cleaning with a NaCl solution with a concentration of 0.1 to 1 mol / L for 10 min to 240 min.
3. The method for preparing room temperature collagen mineralization material according to claim 1, characterized in that: In step S2, the processed fish bubble is fixed on a fixture and stretched flat, and then immersed in a mineralizing solution for mineralization treatment.
4. The method for preparing room temperature collagen mineralized material according to claim 1, characterized in that: In step S2, the mineralization solution is mixed by a calcium source, a phosphorus source, a buffer, sodium chloride, polyacrylic acid and a solvent in a mass ratio of 1:(1-3):(4-8):(20-24):(0.1-0.5):(2200-2500).
5. The method for preparing room temperature collagen mineralization material according to claim 4, characterized in that: The calcium source includes calcium chloride dihydrate; the phosphorus source includes dipotassium hydrogen phosphate trihydrate; the buffer includes hydroxyethylpiperazine ethanesulfonic acid; and the solvent is water.
6. The method for preparing room temperature collagen mineralized material according to claim 1, characterized in that: In step S2, the conditions of the mineralization treatment include: the mineralization temperature is 25-40°C, the mineralization solution is replaced every 12-48 hours, and the total mineralization time is 3-7 days.
7. Room temperature collagen mineralized material obtained by the preparation method according to any one of claims 1 to 6.
8. A block-shaped mineralized collagen material, characterized in that: It comprises a room temperature collagen mineralization material as claimed in claim 7 which is stacked, and adhesive layers are arranged between the layers of the room temperature collagen mineralization material.
9. A method for preparing a block-shaped mineralized collagen material, characterized in that: The following steps are involved: The room temperature collagen mineralized material is laminated, bonded and pressed using biological glue as a binder to obtain a block-shaped mineralized collagen material.
10. The method for preparing a block-shaped mineralized collagen material according to claim 9, characterized in that: The bio-glue is prepared by mixing chitosan, acetic acid and solvent in a mass ratio of 1 g: (5-10) mL: (30-50) mL; the amount of the bio-glue is 0.03-1.3 mL / cm 2 ; The pressing molding is to put the laminated and bonded materials into a vacuum bag, evacuate the bag, and then perform cold isostatic pressing molding; The cold isostatic pressing pressure is 100 MPa to 400 MPa, and the holding time is 5 to 30 min.
Citation Information
Patent Citations
Fish collagen based bionic bone material and preparation method thereof
CN114262374A
Mineralized tendon composite material with prestress as well as preparation method and application of mineralized tendon composite material
CN114732957A
Bone-like multi-level structure composite film material and preparation method and application thereof
CN117883641A